Unraveling Unprecedented Charge Carrier Mobility through Structure Property Relationship of Four Isomers of Didodecyl[1]benzothieno[3, 2‐b][1]benzothiophene. Issue 33 (25th May 2016) - Tsutsui, Yusuke; Schweicher, Guillaume; Chattopadhyay, Basab; Sakurai, Tsuneaki; Arlin, Jean‐Baptiste; Ruzié, Christian; Aliev, Almaz; Ciesielski, Artur; Colella, Silvia; Kennedy, Alan R.; Lemaur, Vincent; Olivier, Yoann; et al.
Abstract : The structural and electronic properties of four isomers of didodecyl[1]‐benzothieno[3, 2‐ b ][1]benzothiophene (C12‐BTBT) have been investigated. Results show the strong impact of the molecular packing on charge carrier transport and electronic polarization properties. Field‐induced time‐resolved microwave conductivity measurements unravel an unprecedented high average interfacial mobility of 170 cm 2 V −1 s −1 for the 2, 7‐isomer, holding great promise for the field of organic electronics.